Alkaloids from Glycosmis cochinchinensis twigs - Tawanun Sripisut (2018)
A phytochemical investigation of the twigs of Glycosmis cochinchinensis led to the isolation of two new alkaloids, glycosmisacridone (1) and glycosmisindole (2), together with eight known compounds (3-10). Their structures were elucidated by intensive analysis of their spectroscopic data. Compound 9 exhibited moderate antibacterial activity against methicillin-resistant Staphylococcus aureus SK1with an MIC value of 16 mg/mL. © 2013 Phytochemical Society of Europe. Published by Elsevier B.V. All rights reserved.